Ethical Perceptions of Accountant: The Role of Professional Ethical Knowledge, God's Locus of Control and Love of Money - Mais, Rimi Gusliana; Nuryati, Tutty (Atestasi : Jurnal Ilmiah Akuntansi, 2023)
This study investigates the impact of accounting students' knowledge of professional ethics on their ethical perceptions, with the moderating variable of the love of money. The study employs SmartPLS software and focuses on accounting students from the 2018 to 2020 classes at various state and private campuses in East Jakarta. The research sample comprises 96 participants who completed a questionnaire distributed online via Google Forms. The findings indicate that while knowledge of professional ethics does not predict ethical perceptions, a God Locus of Control does have a positive effect. Also, Love Of Money was not found to moderate ethical knowledge, but God's Locus of Control impacts ethical perceptions. These results suggest that accounting students must strengthen their knowledge of professional ethics, understand God's Locus of Control, and avoid excessive love of money to become successful and integrated accountants.